High-resolution transcriptional impact of AIRE: effects of pathogenic variants p.Arg257Ter, p.Cys311Tyr, and polygenic risk variant p.Arg471Cys - Berger, Amund Holte; Oftedal, Bergithe Eikeland; Wolff, Anette Susanne Bøe; Husebye, Eystein Sverre; Knappskog, Per Morten; Bratland, Eirik; Johansson, Stefan (Frontiers in Immunology, 2025)
IntroductionThe Autoimmune Regulator, AIRE, acts as a transcriptional regulator in the thymus, facilitating ectopic expression of thousands of genes important for the process of negative T-cell selection and immunological tolerance to self. Pathogenic variants in the gene encoding AIRE are causing Autoimmune polyendocrine syndrome type 1 (APS-1), defined by multiorgan autoimmunity and chronic mucocutaneous candidiasis. More recently, Genome Wide Association Studies (GWAS) have also implicated AIRE in several common organ-specific autoimmune diseases including autoimmune primary adrenal insufficiency, type 1 diabetes and pernicious anemia. MethodsWe developed a highly sensitive cell-system approach based on HEK293FT cells transfected with AIRE that allowed us to characterise and functionally evaluate the transcriptional potential of genetic variants in the AIRE gene. By utilizing RNAseq with an average read depth of 100 million reads and 12 replicates per condition we have the statistical power and sensitivity to characterize the AIRE induced transcriptome in depth. ResultsWe confirm that our cell system recapitulates the expression of the vast majority of known AIRE induced genes including well-characterised tissue restricted antigens (TRAs). Our approach also increases the total number of identified AIRE induced genes by an order of magnitude compared to previously published strategies, including a comprehensive number of clinically relevant autoantigens. DiscussionOur cell-system approach differentiates between categories of AIRE variants on the transcriptional level, including the nonsense variant p.R257* (near complete loss of function), the p.C311Y variant associated with dominantly inherited APS-1 (severely impaired function), and the polygenic risk variant p.R471C (slightly increased function) linked to common organ-specific autoimmunity. The increased activity of p.R471C compared to wildtype indicates different molecular mechanisms for monogenic and polygenic AIRE related autoimmunity. We find that AIRE induced expression is characterised by a small absolute increase in expression levels of genes of both high and low tissue specificity.